Gambaran Tingkat Pengetahuan dan Kepatuhan Pengunaan Obat Kolesterol Di Puskesmas Mulyorejo Kecamatan Sunggal - Debi Dinha Octora; Feronika Sidabutar; Cucu Arum Dwi Cahya; Aminah Syarifuddin (Jurnal Indah Sains dan Klinis, 2022)
Background: Cholesterol and triglycerides above the normal limit, expressed as hyperlipidemia, have a prevalence that increases with age. An unhealthy lifestyle and rarely exercising are the main causes of hyperlipidemia. Objective: The study aims to determine the level of knowledge and compliance with the use of cholesterol medication at the Mulyorejo Community Health Center, Sunggal District. Method: Research uses quantitative descriptive methods. Quantitative descriptive is a measurement whose data is in measurable numbers. Collection of primary data from questionnaires distributed to respondents determined by random sampling. Benefits: Research can be used as evaluation material in the use of anti-cholesterol drugs at the Mulyorejo Community Health Center, Sunggal District. Results: The study obtained from the 50 respondents studied had good knowledge and were compliant with using cholesterol medication, respectively 51.0 and 53.2%; gender, age, education, and occupation are dominated respectively by women (66.0%), 40 -55 years (64%), high school (46%), and employees (30%). Conclusion: This research proves that the community at the Mulyorejo Community Health Center, Sunggal District, has good knowledge and compliance with the percentage of respondents being 51.0 and 53.2% respectively.